2010
DOI: 10.3899/jrheum.100170
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 Gene Polymorphisms Are Associated with Systemic Lupus Erythematosus in Koreans

Abstract: Objective.Interleukin 6 (IL-6) gene polymorphisms are known to play a role in chronic inflammatory disorders. We searched for polymorphisms in theIL-6gene and described their pathogenic role in Korean patients with systemic lupus erythematosus (SLE).Methods.Genomic DNA was extracted from 151 patients with SLE and 151 controls, and about 1.4 kb-sizedIL-6genes located between promoter region and exon 2 region were amplified by polymerase chain reaction. The promoter activity was analyzed by luciferase reporter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Most important is the role of IL-6 as this cytokine has been implicated in multiple autoimmune diseases and directly contributes to plasma cell survival in bone marrow niches (10). In addition, multiple studies in mouse models of SLE have repeatedly demonstrated the importance of IL-6 in driving SLE disease manifestations (3,7,(11)(12)(13). Plasmablasts, precursors of plasma cells, require both APRIL and IL-6, and to a lesser degree BAFF, for full terminal differentiation to bone marrow-derived long-lived plasma cells (LL-PCs) (10,14).…”
mentioning
confidence: 99%
“…Most important is the role of IL-6 as this cytokine has been implicated in multiple autoimmune diseases and directly contributes to plasma cell survival in bone marrow niches (10). In addition, multiple studies in mouse models of SLE have repeatedly demonstrated the importance of IL-6 in driving SLE disease manifestations (3,7,(11)(12)(13). Plasmablasts, precursors of plasma cells, require both APRIL and IL-6, and to a lesser degree BAFF, for full terminal differentiation to bone marrow-derived long-lived plasma cells (LL-PCs) (10,14).…”
mentioning
confidence: 99%
“…14,15,[17][18][19][20][21][22] Moreover, we recently reported that IL-6 promoter polymorphisms are associated with SLE susceptibility and clinical manifestations in Koreans. 10 The 3 0 flanking region of the IL-6 gene is highly polymorphic due to a region of AT repeats that gives rise to VNTR polymorphisms. Genetic association studies revealed associations of IL-6 VNTRs with bone mineral density, Alzheimer's disease, rheumatoid arthritis, and centenarians.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the À278 A > C, 334 A > T, and À373 A n T n polymorphisms of the IL-6 gene were found to be associated with significantly increased disease susceptibility in Koreans with SLE. 10 Furthermore, promoter reporter constructs carrying the -278 C allele displayed significantly higher promoter activity in Hep3B cells and HeLa cells. These data suggest that IL-6 gene polymorphisms are associated with SLE susceptibility through the regulation of IL-6 expression.…”
Section: Introductionmentioning
confidence: 99%
“…ANA is insensitive and is not useful in evaluating disease activity; antidsDNA antibody is highly specific, but its sensitivity is only 57.3% [28,46]. Recently, many researchers have evaluated the use of other autoantibodies in diagnosis and monitoring in patients with SLE.…”
Section: Autoantibodiesmentioning
confidence: 99%
“…IL-6 is a multifunctional cytokine with various biological activities, such as regulation of immune responses, hematopoiesis and the acute phase response, and one of the first cytokines evaluated in lupus pathogenesis due to its close link with B lymphocytes [27,28]. Studies on serum IL-6 in SLE showed that some patients had elevated levels, and these levels correlated with disease activity and anti-dsDNA levels [29,30].…”
Section: Cytokines and Cytokine Receptorsmentioning
confidence: 99%